Ethics in Turkish Nursing Education Programs - Görgülü, Refia Selma (Nursing ethics, 2007)
This descriptive study investigated the current status of ethics instruction in Turkish nursing education programs. The sample for this study comprised 39 nursing schools, which represented 51% of all nursing schools in Turkey. Data were collected through a postal questionnaire. The results revealed that 18 of these nursing schools incorporated an ethics course into undergraduate and three into graduate level programs. Most of the educators focused on the basic concepts of ethics, deontological theory, ethical principles, ethical problems in health care, patient rights and codes of ethics for nurses. More than half of the educators believed that students' theoretical knowledge of ethics is applied to their clinical experiences. The teaching methods used included discussion in class, lectures, case studies, small group discussion, dramatization and demonstration. Assessment was carried out by means of written essays and written examinations.